Monumental Relations: Connecting Memorials and Conversations in Rural and Urban Malanje, Angola - De Grassi, Aharon; Rocha, Manuela (Kronos: Southern African Histories, 2019)
Angola’s staggering oil wealth and histories of conflict and inequality make for tempting binary narratives of power and exploitation, which, however, suffice neither for accuracy nor action. This article uses a relational geographical perspective to go beyond simple binaries by jointly analysing the central 4 February Plaza in the heart of Malanje City, and the proposed new rural memorial for the Baixa de Kassanje revolt located east of the city in Kela Municipality. Drawing on news, ethnography and historical records, I situate the 4 February Plaza in the city’s broader history of settler colonialism and point to its current tensions, ironies and practical and political uses in the city’s daily geography. The Kassanje memorial is relatively unknown and has languished since a first pilot model village was announced by President Agostinho Neto during a 1979 visit. I discuss plans and media coverage about building a Kassanje village project and a new memorial and monument, as well as constructing new housing and social infrastructure in the area. I also examine claims to reestablish 4 January as a national holiday for martyrs of colonial repression (including in Kassanje) and to provide military pensions to people affected by the Kassanje revolt. Analysis shows how such plans and discussion of the revolt reveal both diverse voices in conversation as well as significant changes in dominant narratives about the revolt. More generally, the Kassanje discussions points to rural geographies of nationalism (and their accompanying monuments), which entail their own specificity as well as connections with urban areas. Similarly, understanding both monuments in their provincial contexts – and likewise their connections with Luanda – can provide new perspectives to work that has focused on Luanda and larger cities.